Constituição do Sujeito e Historicidade : um estudo a partir do existencialismo sartreano. - Vaccaro, Marina Menegueti (2013)
The understanding of the subject and the processes that make up its constitution have been over the years the focus and basis of Psychology. The study´s object is rife with difficulties which may be perceived because of its several objectivist or subjectivist approaches. Current research contributes towards the above discussion through a bibliographical research on the manner the existentialism of Jean-Paul Sartre (1905 - 1980) represents the issue of the constitution of the subject and its historicity. Sartre´s theoretical and philosophical works, especially The Transcendence of the Ego (1937), Being and Nothingness (1943), Search for a Method (1960), Critique of Dialectical Reason (1960) and Existentialism is a Humanism (1970), will foreground current investigation. Research was divided into three chapters: (1) Sartre´s Existentialism is presented, coupled to its main influences and its historical and spatial characteristics; (2) Sartre´s concept of the subject and its constitution are investigated; (3) Sartre´s comprehension of human reality by Existential Psychoanalysis and the progressive-regressive method. According to Sartrean existential perspective, the subject is conceived as a body (objectivity) and conscience (subjectivity), but should not be reduced to any of these dimensions. The subject should be understood as a concrete and relational being since it is enmeshed within the world and in constant relationship with the surrounding objectivity, its own body, time, others etc. The above perspective shows that the constitution of the subject occurs through the relationship of the body and conscience with the world. In other words, it occurs through the dialectic relationship between objectivity and subjectivity within the social context. It is due to the construction of the subject within the collective stance that the subject undertakes its own history and also collective history in the same proportion as it is performed by reality. The subject is thus conceived both as the product and the producer: the subject is the producer since in acting on reality, it objectifies itself in the world, constructs its history and collective history. The subject is the product because it subjectivates the objectification of past generations and becomes an objectified subjectivity. This is the reason why, within a Sartrean existential perspective, the constitution of the subject is performed within the dialectics of objectivity and subjectivity.